Adult vernal keratoconjunctivitis. Issue 5 (October 2020) - Di Zazzo, Antonio; Bonini, Stefano; Fernandes, Merle
Abstract : Purpose of review: Vernal keratoconjunctivitis (VKC) is a rare chronic self-limiting allergic inflammatory disease of the ocular surface mostly affecting young boys in their first decade of life. In the last few years a new clinical entity of VKC has been described: adult VKC. Two variants have been identified according to clinical onset: early (childhood VKC persisting beyond puberty) and late onset (arising de novo in adults) adult VKC. Several epidemiologic studies on VKC have been published from single tertiary centers but while the age distribution of VKC patients does show a small percentage of adults with the disease, detailed analysis on this small subset of adult VKC cases is lacking. In this review we describe pathogenesis, clinical features, diagnostic alternatives, and therapeutic alternatives of this highly invalidating disease. Recent findings: Adult variants of VKC have same clinical manifestations of classic form, but show higher inflammatory response and increased risk of chronic fibrotic sequelae. Summary: Adult VKC research could provide insights on the impact of sex hormones in the pathogenesis of allergic diseases and on the mechanisms of inflammation and fibrosis, which cause potentially vision threatening sequelae. The present review will highlight the recent developments in our understanding of this uncommon entity.